Rechtsnormen und Logische Analysis: ein Briefwechsel - Was Kelsen tricked? - Vinicius Magalhães Casagrande (Journal on European History of Law, 2023)
The article aims to uncover the actual discussion that took place between Ulrich Klug and Norbert Wiener, a philosopher of law and a mathematician, on the question of whether it was possible for a machine to apply law using logic. This discussion took place in 1957 and was mentioned by Ulrich Klug in an exchange of letters with Hans Kelsen. Hans Kelsen and Ulrich Klug exchanged letters in which they discussed the application of logic to law. These letters formed the basis for a book entitled Legal Rechtsnormen und logische analyze: ein Briefwechsel 1959 bis 1965. The correspondence between Hans Kelsen and Ulrich Klug was analyzed and from it the correspondence between Klug and Norbert Wiener. The research source comes from Wiener’s personal collection at the Massachusetts Institute of Technology. As a result, we find the letters exchanged between Klug and Wiener. We can conclude that both disagree on the possibility of creating a logical machine that applies the law. From this we can conclude that Klug’s statement to Kelsen that Wiener accepted the existence of a machine that applies the law through logic is false.